2001
DOI: 10.1021/bi011194d
|View full text |Cite
|
Sign up to set email alerts
|

An Engineered Transthyretin Monomer that Is Nonamyloidogenic, Unless It Is Partially Denatured

Abstract: Transthyretin (TTR) is a soluble human plasma protein that can be converted into amyloid by acid-mediated dissociation of the homotetramer into monomers. The pH required for disassembly also results in tertiary structural changes within the monomeric subunits. To understand whether these tertiary structural changes are required for amyloidogenicity, we created the Phe87Met/Leu110Met TTR variant (M-TTR) that is monomeric according to analytical ultracentrifugation and gel filtration analyses and nonamyloidogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
363
0
6

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 225 publications
(394 citation statements)
references
References 43 publications
25
363
0
6
Order By: Relevance
“…Monomeric TTR Variant (M-TTR)-M-TTR was purified according to the above procedure, with slight modifications to the ammonium fractionation step: A 25-90% ammonium sulfate pellet was obtained, resuspended, and dialyzed in 3,500 MWCO Snakeskin dialysis tubing (Pierce Biotechnology, Rockford, Illinois). The typical yield is 40-60 mg of M-TTR from 2 L of cell culture; M-TTR thus obtained is >95% monomeric, as previously reported (19,23).…”
Section: A Tetrameric Ttr Variants (Wt Ttr V30m L55p V122isupporting
confidence: 84%
See 2 more Smart Citations
“…Monomeric TTR Variant (M-TTR)-M-TTR was purified according to the above procedure, with slight modifications to the ammonium fractionation step: A 25-90% ammonium sulfate pellet was obtained, resuspended, and dialyzed in 3,500 MWCO Snakeskin dialysis tubing (Pierce Biotechnology, Rockford, Illinois). The typical yield is 40-60 mg of M-TTR from 2 L of cell culture; M-TTR thus obtained is >95% monomeric, as previously reported (19,23).…”
Section: A Tetrameric Ttr Variants (Wt Ttr V30m L55p V122isupporting
confidence: 84%
“…Generally, rate-limiting tetramer dissociation enables monomer misfolding that is required for TTR to form amyloid (5,(16)(17)(18)(19)(20)(21)(22), by a very efficient downhill polymerization process (23).…”
Section: Published In Final Edited Form Asmentioning
confidence: 99%
See 1 more Smart Citation
“…This intermediate is captured on the unfolding pathways of both V30M and L55P mutants, but not on the pathway of WT-TTR. This observation is supported by the fact that the wild-type monomer is nonamyloidogenic unless the pH is reduced (23), whereas the V30M and L55P mutants can form amyloid protofibrils under physiological conditions after a long incubation (40,60). The wild-type monomeric intermediate which was capable of amyloid deposits at low pH was found to be predominantly a -sheet structure with conformational rearrangements in the C strand-loop-D strand region without a large exposed hydrophobic surface area (16).…”
Section: The Dislocated C Strand-loop-d Strand Intermediate Is On Thementioning
confidence: 90%
“…Moreover, single-point mutations could affect every stage of amyloid formation. Studies of the thermodynamic stability and dissociation kinetics of tetramers have shown that single-point mutations affect the native state stability and/or dissociation barrier (12,22), but dissociation alone is not sufficient for amyloid formation (23). Further tertiary structural changes within a monomer that lead to the monomeric intermediate state are required.…”
mentioning
confidence: 99%